Discovery Learning Through Educandy: Its Effectiveness on Students’ Critical Thinking Ability and Self-Confidence - Saputri, Yunisa Eka; Rusnilawati (Universitas Pendidikan Ganesha, 2023)
Mathematics is an area of knowledge that encourages critical, imaginative, and methodical thinking so that it becomes an integral part of education at all levels, from elementary school to university. Critical thinking and self-confidence are important things that must be mastered by students in learning mathematics. With the discovery learning model using the educandy web it makes learning sweeter. This study aims to analyze the effectiveness of the web-assisted discovery learning model of educandy on critical thinking skills and self-confidence in mathematics in grade IV elementary schools. This type of research uses quantitative research. The method used in this research is quasi-experimental method with Posttest Only Control Group Design. The population of this study consisted of 40 students with a sample of class IVA consisting of 20 students as the experimental class and class IVB consisting of 20 students as the control class. Data on learning motivation was obtained from questionnaire results, while data on learning outcomes was obtained from multiple choice test results. The analysis technique uses descriptive statistics and inferential statistics or t-test. The results of this study indicate that the educandy-assisted discovery learning model influences students' critical thinking skills and self-confidence.